A novel technique for torque ripple suppression in BLDC motor drive using switched capacitor based SEPIC converter - Saha, Sunam; Chowdhury, Debjyoti; Chattopadhyay, Madhurima; Mukherjee, Moumita (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
This article reports a strategy for suppressing commutation torque ripple has been proposed by modifying a SEPIC converter using switched capacitor. The torque ripple generated during the commutation period is one of the main disadvantages of a brushless DC (BLDC) motor. The cause for the torque ripple in brushless DC motor has been mathematically analyzed in this work. Henceforth, a modified switched-capacitor based DC-DC converter has been proposed for integration with BLDC drive. Moreover, a theoretical analysis of the relationship has been established between the duty ratio of the DC-DC converter with commutation time and torque ripple. A low cost and simple method to control the dc link voltage of BLDC drive has been proposed and a comparative analysis of the proposed converter with previously existing similar converters has been shown. This work aims at reducing ripple in electromagnetic torque of BLDC motor from the view point of duty ratio of the DC-DC converter and commutation time of the drive. The feasibility of the drive has been evaluated experimentally and through simulation. It has been observed that the integration of the proposed converter with BLDC drive help in torque ripple suppression to 16.5% as compared to BLDC drive without any DC-DC converter.